PROBLEM-BASED ESP METHODS FOR TEACHING FUTURE AIR TRAFFIC CONTROLLERS TO CONDUCT RADIO EXCHANGE IN NON-ROUTINE SITUATIONS - Bogdana Bystrova; Ludmila Nemliy; Nataliia Paziura; Oksana Vasiukovych (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The research aimed to study and experimentally verify the efficiency of the use of problem-based methods in teaching future air traffic controllers to conduct radio exchange in non-routine situations. The professional readiness to conduct radio exchange is viewed as a complex of professional skills and knowledge (communicative, cognitive and functional) enhanced by motivation. The study involved 67 university students of a bachelor's degree programme majoring in "Aviation transport". Tests, observations and specially designed questionnaires were used to evaluate the use of problem-based methods (role-playing, simulation of specific situations, problem-solving, case studies) in ESP study. The conclusion was made about the effectiveness of problem-based ESP methods since they simulate possible professional situations and promote communication between future air traffic controllers and pilots, thus contributing to the acquisition of professional knowledge and activation of use of standard phraseology of radio exchange and plain English in non-routine situations. As shown by the results of our study, problem-based ESP methods are effective in raising future air traffic controllers' motivation to acquire Aviation English as they bring the learning closer to professional life.